Book review: Shakuntala Rao (Ed.), Indian Journalism in a New Era: Changes, Challenges, and Perspectives. (June 2019) - Sarwatay, Devina
Shakuntala Rao (Ed.), Indian Journalism in a New Era: Changes, Challenges, and Perspectives . New Delhi, India: Oxford University Press, 2019, 396 pp., ₹995 (hbk). ISBN 9780199490820.